(untitled) (Journal of Management and Social Sciences, 2019)
The analyses of constitutions, except in few instances, tend to be legalistic on the basis of examining the structures, functions and perhaps provisions on fundamental human rights that are contained in the document. A section by section legalistic interpretation of constitution making in Nigeria has tended to be devoid of the laying bare of the divergent interests in society in the epoch when the constitution was made and the subsistence of the dominant economic interests. To analyse constitution making in Nigeria this way is faulty. To incorporate an analysis of the dominant interests in society into constitution making is to understand that constitutions are not reflective of the interests of all in society but an instrument to protect property and economic mode of accumulation of the dominant class interests. An analysis of constitution making under the military dictatorships in Nigeria, starting with the 1979 through to the 1989 and 1999 constitutions support the position that these constitutions were made to protect property interests and a capitalist mode of economic accumulation.